PENGARUH STUNTING BAGI PERKEMBANGAN KOGNITIF ANAK - Dinny Rahmayanty; Farah Syaharani; Nurleni Nurleni; Yusuf Ridwan Sholihin (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2024)
Stunting is a common nutritional problem experienced by minors in most developing countries. Stunting has a long-term impact on child development, including cognitive development. This research focuses on examining the impact of stunting on children's cognitive development. The child's nutritional condition and cognitive development are measured and analyzed. Other factors such as the mother's educational level, social status, family economy and access to health services were identified as aspects that could influence children's cognitive development. Therefore, families must prioritize efforts to increase stunting prevention and give stronger special attention to children with nutritional problems. Efforts to improve nutrition and access to health services need to be increased to support optimal development of children's cognitive abilities. This study makes an important contribution to understanding the impact of stunting on children's cognitive development and forms the basis for developing more effective interventions to overcome stunting and improve human resource development.